Effect of food deprivation on neuropeptide Y immunoreactivity and concurrent biochemical and gonadal responses in tilapia Oreochromis mossambicus (Peters, 1852) - ., Vijayalaxmi; Shyamannavar, Bhagyashree; Patil, Supriya; Khaji, N.P.; Ganesh, C.B. (Indian Journal of Fisheries, 2019)
The effect of short- and long-term fasting on neuropeptide Y (NPY) secreting neurons in the brain and concurrent biochemical and gonadal responses were determined in the cichlid fish Oreochromis mossambicus (Peters, 1852). Exposure of fish to fasting for 6 or 12 days resulted in intensely stained NPY-immunoreactive neurons in the nucleus entopeduncularis and the nucleus preopticus regions of the brain in contrast to moderately stained neurons in control fishes, whereas food supplementation after 6 days starvation restored NPY-immunoreactive profile to the same state as in control groups in both male and female fish. The gonadosomatic index remained significantly lower in female fishes subjected to fasting alone as well as fasting followed by refeedings compared to controls. While the hepatosomatic index (HSI) also showed a significant decrease in fasting male and female fish compared to controls, it increased subsequently in fishes exposed to refeeding after starvation. In addition, a significant decrease in the serum levels of glucose and triglycerides as well as the hepatic tissue protein content in fasting fish compared to those of controls in both sexes suggested gluconeogenesis. Although the serum levels of glucose and triglycerides were reinstated in Â both males and female fishes subjected to starvation and refeeding, the hepatic tissue protein levels were not completely restored in females. Collectively, these results suggest that food-deprivation, either for short or long term duration, significantly increases the secretory activity of NPY neurons in the brain concomitant with a significant decrease in the serum levels of glucose and triglycerides, the hepatic tissue protein content and the GSI in both sexes. Although males recovered from the effects of starvation following refeeding, females appeared to be more vulnerable to the effects of fasting. Keywords:Â Â Fasting, Food intake, Neuropeptide Y, Refeeding, Starvation